1960
DOI: 10.1111/j.1365-2141.1960.tb06224.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Erythrocyte Destruction in Haemolytic Anaemia, as Studied with Radioactive Chromium

Abstract: THE introduction of isotope techques and the availability of a suitable isotope label have greatly facilitated the study of the life-span and the sites of destruction of erythrocytes in haemolytic anaemia. Radioactive chromium (51Cr) has several advantages which make it especially suitable for this purpose : the patient's erythrocytes can be labelled and re-introduced into his own circulation, and so studied in their natural environment; chromium liberated by erythrocyte destruction is not uthzed to relabel ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1963
1963
1980
1980

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Recent studies using glycine-2-14C as a label have shown directly that the population sensitive to complement is destroyed within 20 days whereas the insensitive population survives more nearly normally (26). This is in accord with evidence from the 51Cr studies in PNH if the biphasic curve is, in fact, due to the presence of two populations (24).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Recent studies using glycine-2-14C as a label have shown directly that the population sensitive to complement is destroyed within 20 days whereas the insensitive population survives more nearly normally (26). This is in accord with evidence from the 51Cr studies in PNH if the biphasic curve is, in fact, due to the presence of two populations (24).…”
Section: Resultssupporting
confidence: 79%
“…It has been suggested that some of the cells in PNH blood might be normal from the fact that there is a residuum of cells that resists lysis in the acidified serum test even if the cells are exposed to successive samples of acidified serum (22). Also, complex red cell survival curves have been repeatedly noted with PNH cells both with Ashby differential agglutination and radioisotope techniques (23,24). However, it was not known whether this variability in the rate of destruction in vivo and the insensitivity of some of the cells to acidified serum lysis in zitro was a reflection of a single population of cells with a wide distribution in the severity of the abnormality or of two populations of cells.…”
Section: Resultsmentioning
confidence: 99%
“…The autologous red cells of cases 2 and 3 also failed to accumulate predominantly in either the liver or the spleen, which is in keeping with the observation of Lewis, Szur, and Dacie (15). Only in the fourth patient, B. C., was there unequivocal evidence of splenic accumulation of autologous cells.…”
Section: Experimental Methodssupporting
confidence: 69%
“…Measurements of survival of elliptocytes in normals and splenectomized subjects with elliptocytosis (12), re search on elliptocytes tagged with radioactive iron (8) and chro mium (43), and measurements of elliptocyte destruction in cir culating blood (8) all indicate that the spleen has a special role in elliptocyte sequestration and hemolysis very probably similar to that for spherocytes.…”
Section: Discussionmentioning
confidence: 99%